2019
DOI: 10.3390/foods8050175
|View full text |Cite
|
Sign up to set email alerts
|

Viability of 4 Probiotic Bacteria Microencapsulated with Arrowroot Starch in the Simulated Gastrointestinal Tract (GIT) and Yoghurt

Abstract: Probiotic bacteria are usually encapsulated to increase their survival through passage of the simulated gastrointestinal tract (GIT). Four Lactobacilli were freeze-dried and encapsulated with maltodextrin (maltodextrin 1.25 g, whey 0.25 g, bacteria 0.5 g, and water 2 mL) and arrowroot starch (arrowroot 1.25 g, whey 0.25 g, bacteria 0.5 g, and water 2 mL). The effects of different coatings were evaluated for their viability in the GIT and yogurt. The findings indicated no significant differences at p > 0.05 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 42 publications
3
22
0
1
Order By: Relevance
“…Moreover, these small peptides also exhibited the capacity to prevent enteropathogenic Escherichia coli, Salmonella typhimurium, and Shigella flexneri from adhering to intestinal cells [172,173]. Whey proteins, in its different forms, were recently explored as coating materials for the microencapsulation of probiotics [28,30,41,58,72,95,97,[102][103][104][105].…”
Section: Proteinsmentioning
confidence: 99%
“…Moreover, these small peptides also exhibited the capacity to prevent enteropathogenic Escherichia coli, Salmonella typhimurium, and Shigella flexneri from adhering to intestinal cells [172,173]. Whey proteins, in its different forms, were recently explored as coating materials for the microencapsulation of probiotics [28,30,41,58,72,95,97,[102][103][104][105].…”
Section: Proteinsmentioning
confidence: 99%
“…It has been called a “functional food” due to the beneficial action of probiotic bacteria that engage in combat with pathogens, thus improving digestion and intestinal hygiene. To meet modern consumers’ needs, novel variants of yogurt-based products are constantly being investigated and introduced to the market, leading to a steady increase in the sales and popularity of this dairy product [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also used as an additive for probiotic encapsulation. It has the ability to increase weight after digestion in the gastrointestinal tract and maintain the viability of the strain [36]. In addition, previous studies focused on the use of maltodextrin as a carbohydrate supplement as an energy source, and found that it does not affect sports performance [37].…”
Section: Discussionmentioning
confidence: 99%